Genome-Wide Identification of the HD-ZIP III Subfamily in Upland Cotton Reveals the Involvement of GhHB8-5D in the Biosynthesis of Secondary Wall in Fiber and Drought Resistance - Zhang, Jie; Gao, Yanan; Feng, Mengru; Cui, Yuke; Li, Shuaijie; Liu, Le; Wang, Ye; Xu, Wenliang; Li, Fuguang (Frontiers in Plant Science, 2022)
A subfamily of transcription factors known as HD-ZIP III plays distinct roles in the secondary cell wall biosynthesis, which could be attributed to the quality of cotton fiber and adaptation to drought stress. In this study, 18 HD-ZIP III genes were identified as genome wide from the upland cotton (Gossypium hirsutum). These genes are distributed on 14 different chromosomes, and all of them have undergone segmental duplications. Numerous cis-elements were identified in the promoter regions, which are related to phytohormone responses and abiotic stresses. Expression profiling of these genes by quantitative real-time (qRT)-PCR illustrated their differential spatial expression, with preferential expression in cotton fiber. Among these genes, GhHB8-5D was predicted to encode a protein that is targeted to the cell nucleus and having self-activation ability. In addition, the ectopic expression of GhHB8-5D or its synonymous mutant GhHB8-5Dm in Arabidopsis resulted in stunted plant growth, curly leaves, and twisted inflorescence stems. Microscopy examination revealed that the morphology of vascular bundles and deposition of secondary wall had substantially altered in stems, which is concomitant with the significant alteration in the transcription levels of secondary wall-related genes in these transgenic Arabidopsis. Further, ectopic expression of GhHB8-5D or GhHB8-5Dm in Arabidopsis also led to significant increase in green seedling rate and reduction in root length relative to wild type when the plants were grown under mimicked drought stress conditions. Taken together, our results may shed new light on the functional roles of GhHB8-5D that is attributable for secondary cell wall thickening in response to drought stress. Such a finding may facilitate a novel strategy for improving plant adaptations to environmental changes via regulating the biosynthesis of secondary cell wall.